Airway Remodelling in Asthma: From Benchside to Clinical Practice. Issue 4 (2010) - Bergeron, Céline; Tulic, Meri K; Hamid, Qutayba
Abstract : Airway remodelling refers to the structural changes that occur in both large and small airways relevant to miscellaneous diseases including asthma. In asthma, airway structural changes include subepithelial fibrosis, increased smooth muscle mass, gland enlargement, neovascularization and epithelial alterations. Although controversial, airway remodelling is commonly attributed to an underlying chronic inflammatory process. These remodelling changes contribute to thickening of airway walls and, consequently, lead to airway narrowing, bronchial hyper-responsiveness, airway edema and mucous hypersecretion. Airway remodelling is associated with poor clinical outcomes among asthmatic patients. Early diagnosis and prevention of airway remodelling has the potential to decrease disease severity, improve control and prevent disease expression. The relationship between structural changes and clinical and functional abnormalities clearly deserves further investigation. The present review briefly describes the characteristic features of airway remodelling observed in asthma, its clinical consequences and relevance for physicians, and its modulation by therapeutic approaches used in the treatment of asthmatic patients.